Advanced X‐ray Absorption Spectroscopy Analysis to Determine Structure‐Activity Relationships for Cu‐Zeolites in the Direct Conversion of Methane to Methanol. Issue 9 (2nd April 2020) - Kvande, Karoline; Pappas, Dimitrios K.; Borfecchia, Elisa; Lomachenko, Kirill A.
Abstract: An industrial process for direct conversion of methane to methanol (DMTM) would revolutionize methane as feedstock for the chemical industry and it would be a cherished contribution to climate change mitigation. At the present stage, it is a rather remote perspective, but the search for the materials that would make it possible and economically viable, is very active. Cu‐exchanged zeolites have been shown to cleave the C−H bond of methane at low temperatures (≤200 °C), and has been extensively studied for the stepwise DMTM conversion over the last decades. The determination of the speciation of Cux Oy ‐species in zeolites and the understanding of their role in the reaction mechanism has been heavily debated. Lately, advanced X‐ray absorption spectroscopy (XAS) analysis has been standing out as a powerful technique for investigating the behavior of Cu in zeolites. In this review we focus on the in situ and operando studies of changes in the electronic and structural properties of Cu, during the different steps of the DMTM conversion uncovered by XAS, which have led to new and insightful information about the complex behavior of Cu‐zeolites in the DMTM process. Abstract : X‐ray absorption spectroscopy (XAS) is a powerful technique for investigating the active sites of nanoporous catalysts by following their structural and electronic changes under in situ and operando conditions. This review summarizes the recent XAS studies that focus on the speciation and reducibility of Cu centers in Cu‐exchanged zeolites, providing mechanistic insights for the direct conversion of methane to methanol.